Analysis Of The Implementation Of The Subsidized Fertilizer Program In Gapoktan Gurun Raya - Atifa, Saydatul; Alfikri; Arnayulis; Lailatul Mubarokah, Syaima (Universitas Djuanda, 2025)
This study aims to analyze the implementation of the subsidized fertilizer program in Gapoktan Gurun Raya, Nagari Gurun, Harau District, Lima Puluh Kota Regency. The focus of the study is the effectiveness of the program based on the principle of 6 Tepat (Quantity, Place, Price, Time, Type, and Quality). The method used is a qualitative approach with primary data collected through in-depth interviews, field observations, and structured questionnaires to 40 farmers who are members of 4 farmer groups in Gapoktan Gurun Raya. Secondary data was obtained from the Gapoktan archives and other related sources. The results of the study indicate that the implementation of the subsidized fertilizer program in Gapoktan Gurun Raya as a whole is quite effective with an average satisfaction of above 60% in almost all indicators. However, the